Pancreatitis aguda secundaria a hipertrigliceridemia: presentación de dos casos clínicos (2008)
The acute pancreatitis is a reversible inflammatory process. Hypertriglyceridemia as etiology of the acute pancreatitis reaches frequencies you enter 1.3 11% according to Literature when the triglycerides levels of reach values over 1000 mg/dl; nevertheless Hypertriglyceridemia is observed in 12 39% of the acute pancreatitis like factor associate. The objective of the medical treatment is to increase the activity of lipoproteinlipasa and to increase the degradation of chylomicrones; diminishing therefore the serum triglycerides values of at levels smaller to 500 even to less of 200mg/dl if it is possible with different strategies, among them the insulin. In the present article, we presented/displayed two clinical cases of severe pancreatitis induced by Hypertriglyceridemia, handled with therapy of insulin infusion with suitable evolution and clinical answer given by significant diminution of the levels of triglycerides, 48 hours post treatment. © Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.